2019
DOI: 10.3892/mmr.2019.10428
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA DLEU1 promotes cell proliferation of glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common malignant tumor with high morbidity and mortality. This study investigated the role of long non-coding rnas (lncrnas) in glioblastomagenesis progression. using the GSe2223 and GSe59612 datasets, and rna sequencing data of GBM from The cancer Genome atlas, differentially expressed (de) genes including de messenger rnas (demrnas) and delncrnas between GBM and normal controls were identified. Based on the competing endogenous RNA hypothesis, delncrna-micro rna (mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Further determination of the key gene requires a combination of its expression, typicality in previous studies, and previous research experience in our lab. Among the 14 candidate genes we selected, most genes have been confirmed to be related to the prognosis of GBM, such as: SPAG4, FKBP1B, DLEU1, PRKAR2B, NRL, CD24, GAS6; some genes have not been clearly studied to be related to the occurrence of any known tumors, such as CAMSAP2; the remaining genes have not been significantly expressed in GBM, such as CORO6 ( Lo et al, 2009 ; Sun et al, 2021 ; Wang et al, 2019 ; Zhao et al, 2019 ). Finally, we found that four genes (DARS/GDI2/P4HA2/TRUB1) had an impact on the survival rate of patients with GBM, and were also confirmed to be related to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Further determination of the key gene requires a combination of its expression, typicality in previous studies, and previous research experience in our lab. Among the 14 candidate genes we selected, most genes have been confirmed to be related to the prognosis of GBM, such as: SPAG4, FKBP1B, DLEU1, PRKAR2B, NRL, CD24, GAS6; some genes have not been clearly studied to be related to the occurrence of any known tumors, such as CAMSAP2; the remaining genes have not been significantly expressed in GBM, such as CORO6 ( Lo et al, 2009 ; Sun et al, 2021 ; Wang et al, 2019 ; Zhao et al, 2019 ). Finally, we found that four genes (DARS/GDI2/P4HA2/TRUB1) had an impact on the survival rate of patients with GBM, and were also confirmed to be related to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…High expression of TRAF4 significantly increased cyclinD1 and c-myc protein expression levels in cancer cells and activated the Wnt/β-catenin signaling pathway ( 75 ). DLEU1 can act as a competitive endogenous RNA that promotes elevated TRAF4 expression levels, promotes cancer cell proliferation through the Hippo signaling pathway and Wnt/β-catenin signaling pathway and regulate cell migration ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression levels of DLEU1 and TRAF4 in glioblastoma multiforme (GBM) tissues promote GBM cell proliferation and regulate cell migration through the Hippo signaling pathway and Wnt signaling pathway. DLEU1 in GBM can act as a competitive endogenous RNA, thereby promoting GBM tumorigenesis ( 79 ).…”
Section: Regulatory Role In Other Tumorsmentioning
confidence: 99%
“…Glioma is the most common type of primary brain tumor, accounting for 51.4% of all primary brain tumors, and glioblastoma is the most aggressive glioma, with high mortality in adults. 111,112 In the GSE2223 and GSE59612 datasets Wang et al 113 screened 712 lncRNAs dysregulated in glioblastoma multiforme compared with normal control tissues. Among these lncRNAs, DLEU1 was found to be significantly upregulated and to interact with 315 miRNAs and 105 mRNAs associated mainly with tumorigenesisrelated terms and pathways, including the Hippo signaling pathway.…”
Section: Central Nervous System Tumorsmentioning
confidence: 99%